Gut microbiota and its derived SCFAs regulate the HPGA to reverse obesity-induced precocious puberty in female rats - Wang, Li; Xu, Hao; Tan, Bin; Yi, Qin; Liu, Huiwen; Deng, Hongrong; Chen, Yunxia; Wang, Rui; Tian, Jie; Zhu, Jing (Frontiers in Endocrinology, 2022)
The intestinal microbiota and its derived short-chain fatty acids (SCFAs) can reverse obesity and obesity-related metabolic diseases, but whether it has an effect on obesity complicated by precocious puberty and its potential mechanism need to be further understood. The purpose of this study was to investigate the effect of the gut microbiota and its derived short-chain fatty acids (SCFAs) on obesity-induced precocious puberty rats and their regulatory mechanisms. We constructed obesity-induced precocious puberty rats using a high-fat diet (HFD) had notable similarity to precocious puberty caused by obesity due to overeating in children. We then added acetate, propionate, butyrate or their mixture to the HFD, and investigated the effect of intestinal microbiota and its derived SCFAs on the hypothalamic-pituitary-gonadal axis (HPGA) in rats with obesity-induced precocious puberty. We found that obesity-induced precocious puberty rats had an early first estrous cycle, increased hypothalamic mRNA expression of Kiss1, GPR54 and GnRH, and early gonadal maturation. Meanwhile, the intestinal microbiota imbalance and the main SCFAs production decreased in the colon. The addition of acetate, propionate, butyrate or their mixture to the HFD could significantly reverse the precocious puberty of rats, reduce GnRH release from the hypothalamus and delay the development of the gonadal axis through the Kiss1–GPR54–PKC–ERK1/2 pathway. Our findings suggest that gut microbiota-derived SCFAs are promising therapeutic means for the prevention of obesity-induced precocious puberty and provide new therapeutic strategies with clinical value.